Effects of Whole Body Cryotherapy and Cold Water Immersion on Knee Skin Temperature - Costello, J. T.; Donnelly, A. E.; Karki, A.; Selfe, J. (International Journal of Sports Medicine, 2014)
This study sought to a) compare and contrast the effect of 2 commonly used cryotherapy treatments, 4 min of −110°C whole body cryotherapy and 8°C cold water immersion, on knee skin temperature and b) establish whether either protocol was capable of achieving a skin temperature (<13°C) believed to be required for analgesic purposes. After ethics committee approval and written informed consent was obtained, 10 healthy males (26.5±4.9 yr, 183.5±6.0 cm, 90.7±19.9 kg, 26.8±5.0 kg/m2, 23.0±9.3% body fat; mean±SD) participated in this randomised controlled crossover study. Skin temperature around the patellar region was assessed in both knees via non-contact, infrared thermal imaging and recorded pre-, immediately post-treatment and every 10 min thereafter for 60 min. Compared to baseline, average, minimum and maximum skin temperatures were significantly reduced (p<0.001) immediately post-treatment and at 10, 20, 30, 40, 50 and 60 min after both cooling modalities. Average and minimum skin temperatures were lower (p<0.05) immediately after whole body cryotherapy (19.0±0.9°C) compared to cold water immersion (20.5±0.6°C). However, from 10 to 60 min post, the average, minimum and maximum skin temperatures were lower (p<0.05) following the cold water treatment. Finally, neither protocol achieved a skin temperature believed to be required to elicit an analgesic effect.
Keywords: cryotherapy; skin temperature; tissue temperature; knee; cryokinetics